Indicators on global value chains A guide for empirical work - Ahmad, Nadim (OECD Statistics Working Papers, 2017)
Traditionally, the main source of data used to measure countries' participation in international production networks or global value chains (GVCs) has been conventional international trade statistics. However, international fragmentation of production has weakened the analytic interpretability of these data as intermediate goods but also services cross borders many times on the way to their final destination. This is often referred to as the double (or multiple)-counting problem of international trade Statistics. This, in turn, has led to the development of a new branch of trade statistics, referred to as Trade in Value-Added (TiVA) providing new insights on GVCs, and corresponding databases, notably the OECD-WTO TiVA database, which provide a measure of international interdependencies through the construction of global input-output tables that show how producers in one country provide goods and/or services to producers and consumers in others. But with the field still relatively new, many users are struggling to fully understand how these new indicators should be used and indeed how they have been constructed. This document is designed to address those difficulties, providing, where appropriate guidance on "dos" and "don'ts". It also reviews many other typical GVC indicators derived outside of input-output frameworks; recognising that gross measures of trade, and indicators derived from them, remain important and relevant for policy making